Modelagem fotogramétrica e calibração de um sistema de visão omnidirecional - Marcato Junior, José [UNESP] (2014)
Omnidirectional vision systems that enable 360° imaging have been widely used in several research areas including Close-Range Photogrammetry. The use of this system to acquire accurate measurement, which is the aim of Photogrammetry, requires two steps: sensor and platform mathematical modelling, relating features in the object space with the features in the image space; and the system calibration, in which the mathematical models parameters are estimated. The main aim is to develop the rigorous photogrammetric modelling and a calibration technique to an omnidirectional system composed of a camera and a conic mirror. The relationship between the object and image spaces is established using point features. The mathematical modelling is based on the camera projection model and on the properties of the conic mirror reflection. The system calibration technique is divided into inner and platform calibration. The inner calibration technique has the following steps: camera calibration; conic mirror modelling; and estimation of the parameters which relates the camera and cone reference systems. In the platform calibration, the parameters relating the imaging system and the direct georeferencing system, composed of a GNSS (Global Navigation Satellite System) receiver and an IMU (Initial Measurement Unity), were estimated...